P5-S1.04 The impact of pelvic inflammatory disease on sexual, reproductive and psychological health. (10th July 2011) - Hocking, J; Newton, D; Bayly, C; Fairley, C; Chen, M; Williams, H; Keogh, L; Temple-Smith, M; McNamee, K; Fisher, J; Hsueh, A; Hocking, J
Abstract : Background and Aim: Pelvic inflammatory disease (PID) is a condition commonly attributable to chlamydia infection. This qualitative study sought to explore the sexual, reproductive and psychological impact of this condition. Methods: In depth, semi-structured interviews were conducted with 23 women diagnosed with PID. Both symptomatic and asymptomatic women were recruited from primary and tertiary healthcare services. Interviews were conducted with women from 2 to 12 months post-diagnosis in order to explore short and longer term psychological responses and experiences. A brief, self-report questionnaire containing demographic items was also completed by all women. Interview analysis was conducted using an inductive, thematic approach. Results: Nearly all women experienced some form of distress when they received their diagnosis, and the emotional impact of their diagnosis was generally prolonged. Women typically experienced emotions such as shock, sadness or anger. At the time of diagnosis, women frequently had little or no knowledge of PID and continued to experience confusion about their condition post-diagnosis. Some women reported that PID had created conflict in their intimate relationships or had impacted on the level of intimacy they shared with their partner. Almost all women reported that their sexual behaviour had changed dramatically post- diagnosis. The possibility of being infertile stood out for women as their greatest health concern and nearly all women reported changes to their health behaviours since their diagnosis. Conclusion: The findings of this study indicate that a diagnosis of PID can have significant psychosocial implications for the diagnosed individual. Recommendations for healthcare professionals are proposed.